Urinary tract stone disease - Nagaraja Rao, P. 1910-; Preminger, Glenn M.; Kavanagh, John P. (Springer, 2011)
Urinary Tract Stone Disease covers the entire subject of urinary stone disease from basic sciences to medical and surgical treatment of stones. The surgical management of urinary stone disease has advanced significantly since the introduction of shock wave lithotripsy (SWL), percutaneous nephrolithotomy (PCNL), ureteroscopy (URS), and more recently retrograde intra-renal surgery (RIRS) with small, flexible fibre-optic ureteroscopes. As a result, cutting for stones has become a rare procedure. These minimally invasive techniques are now also used in the paediatric population with great safety and success. This book consists of 60 chapters divided into 9 sections. The first 3 sections are devoted to basic sciences on subjects ranging from epidemiology of urinary calculi, to shock wave physics. The fourth section deals with diagnostic, laboratory, and research methods in the diagnosis and investigation of stones. Stone disease in children is dealt with in chapter 5, followed by 3 sections on surgical management of stones. Finally, there is an entire section on medical management of stones. With highly illustrated diagrams, photographs, and X-ray images throughout, this book is an excellent reference for urologists, nephrologists and non-medical scientists.